ANALISA TINGKAT KEPENTINGAN WELDING PROCESS SPECIFICATION PROCEDURE DALAM MENJAMIN KESELAMATAN KERJA PEKERJA PADA PROSES PEKERJAAN PENGELASAN DI PT.M.E.I - ediyansyah; Rissetridharma Simanjuntak (Mechanical Engineering Departement - Universitas Tridharma, 2020)
On Industrial or manufacture world or oil and mining the welding is becoming theone of important part which can be separating in the company. Where the welding process as the separating case in growing raise industry so it because the welding has handled in the main of metal production process. As the welder on the welding process must be attention on their job safety and healthy, and that’s needed. The welder must be attention the welding process specification.cases which was needed so it will taking care themselves and because of that the job safety will implementation in working area. On the electric welding many maters coming it became danger and need more attention for the welder self , electric welding machine, and the people. The cases namely the fire flower spark, electric welding smoke and poisonous dust, ultra violet rays radiation effects , and electric welding ultra red. Keywords — healthy and safety, welding, electric welding, procedure